Biochemical and structural studies on the PhoR-PhoB two-component regulatory system from Deinococcus radiodurans - Caria, Sofia (2010)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2010.